Indirect translation and the influence of the mediating text : the case of Le Petit Prince in Malay - Haslina Haroon (Penerbit Universiti Kebangsaan Malaysia, 2022)
An indirect translation is a translation that is carried out based on a text which is also a translation. The source text for the indirect translation is therefore the text that mediates between the indirect translation and the original or ultimate source text. Considering the fact that an indirect translation is twice removed from the ultimate source text, a pertinent issue arising from this practice is whether there are differences between the indirect translation and the ultimate source text because of the use of the mediating text. This paper aims to explore this issue by comparing and analysing three texts: a French source text entitled Le Petit Prince, the English mediating text entitled The Little Prince, and an indirect translation in Malay entitled Putera Cilik. A comparison of the three texts first necessitates the mapping of each sentence of the Malay translation to its counterparts in English and in French. An analysis is then carried out on the sets of texts to determine whether there are discrepancies between the Malay translation and the French text. The findings show that generally, the Malay translation closely reflects the French source text. Where discrepancies do exist between the Malay translation and the French source text due to adjustments made in the translation, the English mediating text does play a role. It is, however, not necessarily the sole contributing factor, as some of the discrepancies can also be attributed to the translator of the target text.